2018
DOI: 10.1111/jgh.14402
|View full text |Cite
|
Sign up to set email alerts
|

Over‐the‐scope clip system: A review of 1517 cases over 9 years

Abstract: Rescue therapy for gastrointestinal (GI) refractory bleeding, perforation, and fistula has traditionally required surgical interventions owing to the limited performance of conventional endoscopic instruments and techniques. An innovative clipping system, the over-the-scope clip (OTSC), may play an important role in rescue therapy. This innovative device is proposed as the final option in endoscopic treatment. The device presents several advantages including having a powerful sewing force for closure of GI def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
154
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 64 publications
(107 reference statements)
3
154
1
5
Order By: Relevance
“…A similar multicenter cohort study (n = 188) included 10 patients with esophageal iatrogenic perforation, all treated successfully with OTS clipping [33]. A large systematic review of patients all treated with OTS clipping (n = 1517 cases; total GI perforations, n = 351) concluded that the mean success rate when using OTS clips for treatment of perforation was 84.6 % (297/351 cases) [37]. These results included perforations throughout the GI tract; nevertheless, iatrogenic perforation in the esophagus may be difficult to close because of the tubular esophageal anatomy [37,76].…”
Section: Treatment: Esophagusmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar multicenter cohort study (n = 188) included 10 patients with esophageal iatrogenic perforation, all treated successfully with OTS clipping [33]. A large systematic review of patients all treated with OTS clipping (n = 1517 cases; total GI perforations, n = 351) concluded that the mean success rate when using OTS clips for treatment of perforation was 84.6 % (297/351 cases) [37]. These results included perforations throughout the GI tract; nevertheless, iatrogenic perforation in the esophagus may be difficult to close because of the tubular esophageal anatomy [37,76].…”
Section: Treatment: Esophagusmentioning
confidence: 99%
“…A large systematic review of patients all treated with OTS clipping (n = 1517 cases; total GI perforations, n = 351) concluded that the mean success rate when using OTS clips for treatment of perforation was 84.6 % (297/351 cases) [37]. These results included perforations throughout the GI tract; nevertheless, iatrogenic perforation in the esophagus may be difficult to close because of the tubular esophageal anatomy [37,76]. Hagel et al concluded that defects located in the proximal and mid esophagus, greater than 20 mm in size, with ischemic or congested margins, or present for longer than 72 hours, were least amenable to OTS clip closure [76].…”
Section: Treatment: Esophagusmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of the over‐the‐scope clip (OTSC) system is safe and effective for hemostasis in gastrointestinal bleeding, closure of fistula, iatrogenic gastrointestinal perforations, and preventing delayed perforation after duodenal endoscopic resection . Furthermore, we developed a novel endoscopic mucosal resection method with OTSC (EMRO) .…”
Section: Brief Explanationmentioning
confidence: 99%